Temperature and Moisture-Deformations of High-Temperature-Resistant Concrete Under Single Impact of Water and Temperature - Abdurahmonov Adkhamjon Sultonboyevich (PT ANTIS International Publisher, 2024)
In article results an experimental research of work of the vnetsentrenno-stretched ferro-concrete beams from heavy concrete and from concrete on straining cement are resulted at simultaneous action of longitudinal stretching effort, temperatures and waters.